PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPA - Herlina, Ayu (PRODI PGSD UNIVERSITAS PGRI DELTA, 2023)
This study is motivated by the low ability of students in critical thinking, aims to improve students' critical thinking skills in learning science material on changes in the form of objects by using the Problem Posing learning model. This research is a class action research where the researcher collaborates with the fifth grade teacher of SDN 138 Gegerkalong Girang. Class V students totaled 24 students with 12 female students and 12 male students. The techniques used in data collection in this study were tests, observation and documentation. The instruments used consisted of evaluation sheets (questions) and observation sheets of student activities, observation sheets of teacher activities and photographs. The data obtained in the form of test results and observation results as primary data and documentation as secondary data. The data analysis technique used was quantitative descriptive analysis to analyze the final test of each cycle and qualitative descriptive analysis for the observation results of each cycle. This research was conducted in two cycles using a research design that refers to Kemmis and Mc Taggart. The results showed that the use of Problem Posing learning model can improve students' critical thinking skills. This is indicated by an increase in scores from cycle I to cycle II. Cycle I showed that only 13 students were complete or 54.16%. After implementing cycle II, students' critical thinking skills increased to 83.33% or there were 20 students who were complete. Observation of student activities showed an increase in each cycle. In cycle I it reached 72.22%, while in cycle II it reached 83.33%. Observation of teacher activities in cycle I reached 80%, while in cycle II it increased to 93.33%. Thus, the use of the Problem Posing learning model can improve students' critical thinking skills in grade V students of SDN 138 Gegerkalong Girang. It is also recommended to elementary school teachers to always use this Problem Posing learning model in other learning materials.